2017
DOI: 10.1002/hyp.11207
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of agricultural sediment and pesticide runoff: RZWQM and PRZM comparison

Abstract: Agricultural sediment and pesticide runoff is a widespread ecological and human health concern.Numerical simulation models, such as Root Zone Water Quality Model (RZWQM) and Pesticide Root Zone Model (PRZM), have been increasingly used to quantify off-site agricultural pollutant movement. However, RZWQM has been criticized for its inability to simulate sedimentation processes. The recent incorporation of the sedimentation module of Groundwater Loading Effects of Agricultural Management Systems has enabled RZWQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Soil hydraulic parameters were calibrated to optimize the simulation of soil water content within a 1.2‐m profile. Field capacity and K s were the sensitive parameters that affected runoff and soil profile water storage (Chen et al., 2017). We observed that soil water balance was highly sensitive to the K s value of the top 5‐cm horizon.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Soil hydraulic parameters were calibrated to optimize the simulation of soil water content within a 1.2‐m profile. Field capacity and K s were the sensitive parameters that affected runoff and soil profile water storage (Chen et al., 2017). We observed that soil water balance was highly sensitive to the K s value of the top 5‐cm horizon.…”
Section: Methodsmentioning
confidence: 99%
“…The NNSE was calculated by normalizing Nash–Sutcliffe efficiency (NSE) within a 0–1 range [NNSE = 1/(2‐NSE)]. Generally, R 2 ≥ 0.5, NNSE > 0.5, d ≥ 0.5, and |PBIAS| ≤ 50% were considered acceptable (Bennett et al., 2013; Chen et al., 2017). For performance evaluation, whole seasonal soil water data including 60 days of calibration were used in the 2019–2020 and 2020–2021 simulation periods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In many practical situations where not many data are available, using a simple model with fewer parameters is recommended [21]. Numerical modeling to simulating pesticide behavior is an attractive way to perform environmental assessment of agricultural situations [22][23][24][25]. As the first step of the assessment process, it is necessary to identify which pesticide should be used for a specific climate-crop-soil combination, as well as its application rates, so that both crops and the environment are protected.…”
Section: Introductionmentioning
confidence: 99%